التوصيف الشكلي وتقييم بعض الطرز المظهرية للنوع خوخ الدب Prunus ursina K.y في الساحل السوري (Latakia University Journal -Biological Sciences Series, 2016)
نفذ هذا البحث خلال العامين 2011 و2013 بهدف تحديد بعض الموصفات الكمية والنوعية لبعض أشجار خوخ الدب Prunus ursina K.y المنتشرة في مناطق مختلفة من الساحل السوري. حددت سبعة مواقع طبيعية لوجود وانتشار تلك الأشجار، ومن ثم حددت(43) شجرة لإجراء الدراسة عليها، استخدمت القياسات الحيوية على 22 صفة لأجزاء النبات المختلفة (أوراق- أزهار- ثمار- نوى). بين التحليل الإحصائي للصفات الكمية والنوعية للطرز المدروسة توزع تلك الأشجار ضمن خمس مجموعات ( A-B-C-D-E)اعتبرت كل منها طرازا مظهريا. وقد أظهرت النتائج انتشار طراز مظهري واحد في عدة مواقع مثل الطرز (C-D-E) التي انتشر كل منها على حدة في أكثر من موقع، بينما الطرازين (A-B) انتشرا في موقع واحد حيث ظهر الطراز (A) على شجرة واحدة فقط دون غيرها في موقع النبعين في حين ظهر الطراز (B) في موقع بتمازة على نصف الأشجار المدروسة فقط بينما توزع النصف الآخر ضمن الطراز (D).This study was carried out during 2011- 2013 to determine some qualitative and quantitative features of some distribution trees of Prunus ursina in different regions of Syrian coast.7 natural distribution sites were determined and 43 trees were determined as samples.22 features of different plant portions were studied using biological measurements(leaves, flowers, fruits, seeds). Statistical analysis of investigated phenotypes showed that trees were distributed in 5 groups (A, B, C, D, E) each one considered phenotype. The results showed existence of one phenotype in several sites (C, D, E) while (A and B) phenotypes were distributed in one site, while (A) phenotype was located in one tree only in " Nabeen" site whereas (B) phenotype was located on only half investigated trees in "Btmaze" site, while the other half distributed in (D) phenotype.